The Dialectical Relationship Between Language, Thought and Culture and its Impact on Lexical Interpretation The Interpretation of the Term 'Manliness’ in Al-Ain' Dictionary and the Dictionaries Followed as a Model - Nasir Talib, Lect . Dr. Anfal (Basra studies journal, 2025)
The current paper deals with the reciprocal relationship between language, thought, and culture and its influence on the interpretation of the lexical items in Arabic dictionaries .in the light of Whorf-Sapir hypothesis which is based on the duality of linguistic relativity and linguistic determinism. The researcher traces this reciprocal relationship in the interpretation of the lexical item 'nobility' in Al-Ain Dictionary and in the subsequent dictionaries in order to reveal the reflection of the community culture in Al Khaleel's interpretive linguistic blog in his dictionary on one hand and the transmission of the inherited cultural influence to the interpretations across generations in the subsequent dictionaries that followed Al Khaleel's example. without deviation, on the other hand. The most prominent conclusion the present paper has arrived at is that there is a reciprocal influence between language, thought, and culture. Culture is stored in the collective mind of the members of the society and is revealed in their language just as language affects the way the members of a society think and see the word.